Predictive value of preoperative serum squamous cell carcinoma antigen level for lymph node metastasis in early-stage cervical squamous cell carcinoma. Issue 33 (20th August 2021) - Zhu, Chenggong; Zhang, Wenqing; Wang, Xiuying; Jiao, Lanzhou; Chen, Liyan; Jiang, Jiyong
Abstract : Abstract: To explore the predictive value of preoperative serum squamous cell carcinoma antigen (SCC-Ag) level for lymph node metastasis (LNM), particularly, in patients surgically treated for early-stage cervical squamous cell carcinoma. We enrolled 162 patients with cervical squamous cell carcinoma stages IB to IIA following the International Federation of Gynecology and Obstetrics (FIGO) 2009 classification. The patients had previously undergone radical surgery. Correlation of the SCC-Ag level with clinicopathological features and the predictive value of SCC-Ag for LNM were analyzed. High preoperative SCC-Ag level was correlated with FIGO stage ( P = .001), tumor diameter >4 cm ( P < .001), stromal infiltration ( P < .001), LNM ( P < .001) and lymphovascular space invasion (LVSI), ( P = .045). However, it was not correlated with age, histological differentiation, parametrial involvement, and positive vaginal margin ( P > .05). Univariate analysis revealed that FIGO stage ( P = .015), tumor diameter ( P = .044), stromal infiltration (χ 2 = 10.436, P = .005), SCC-Ag ≧ 2.75 ng/mL (χ 2 = 14.339, P < .001), LVSI (χ 2 = 12.866, P < .001), parametrial involvement (χ 2 = 13.784, P < .001) were correlated with LNM, but not with age, histological differentiation, and positive vaginal margin. Moreover, multivariate analysis demonstrated that SCC-Ag ≧2.75 ng/mL ( P = .011, OR = 3.287) and LVSI ( P = .009, OR = 7.559) were independent factors affecting LNM. The area under the receiver operator characteristic curve of SCC-Ag was 0.703 ( P < .001), while 2.75 ng/mL was the best cutoff value for predicting LNM. The sensitivity and specificity of diagnosis were 69.4% and 65.9%, respectively. High SCC-Ag level was revealed to be an independent risk factor for the prognosis of squamous carcinoma of the cervix before an operation. Besides, SCC-Ag (2.75 ng/mL) can be utilized as a potential marker to predict LNM in early stage cervical cancer before an operation.